Photocatalysed oxidation of cyclohexane by W10O32−4 irradiation with natural sunlight - Charles Giannotti; Christoph Richter (International Journal of Photoenergy)
Using global sun UV-emission, dioxygen, W10O32−4 as a photocatalyst in acetonitrile solution we have performed cyclohexane oxidation. Such photooxidation was very effective and could be applied in a large scale. The best result was obtained using 20% acetonitrile/cyclohexane emulsion and W10O32Na4 as a catalyst.